Porous carbon coated cobalt elementary substance / niobium carbide heterojunction material as well as preparation method and application thereof

By using porous carbon coated cobalt elemental/niobium carbide heterojunction material as sulfur-based positive electrode carrier in lithium-sulfur batteries, the problems of conductivity and volume changes in lithium-sulfur batteries are solved, and the electrochemical performance and cyclic stability of the battery are improved.

CN120261578APending Publication Date: 2025-07-04FUDAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510416292.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

The practical application of existing lithium-sulfur batteries is negatively affected by factors such as the adverse conductivity characteristics of the electrochemically active substances sulfur and lithium sulfide, the change in the electrode volume during charging and discharging, the shuttle effect of the intermediate product long-chain lithium polysulfide in the ether-based electrolyte, and the hysteresis kinetics, resulting in insufficient performance.

Method used

Porous carbon coated cobalt elemental/niobium carbide heterojunction material is used as the sulfur-based positive electrode support, and the cobalt elemental/niobium carbide heterojunction is uniformly dispersed on the porous carbon, using the high specific surface area and rich pore structure of porous carbon, combining the interface charge rearrangement of cobalt elemental/niobium carbide heterojunction to enhance the activity of the adsorption-catalytic center.

Benefits of technology

It effectively improves the electrochemical performance of lithium sulfur batteries, promotes the conversion kinetics of lithium polysulfide, inhibits the shuttle effect, and improves the sulfur-carrying capacity of the sulfur-based positive electrode and the cycling stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120261578A_ABST
    Figure CN120261578A_ABST
Patent Text Reader

Abstract

The invention relates to a porous carbon coated cobalt elementary substance / niobium carbide heterojunction material as well as a preparation method and application thereof. The material comprises polyhedral hollow nitrogen-doped porous carbon and elemental cobalt / niobium carbide heterojunctions uniformly dispersed on the porous carbon. The preparation method comprises the following steps: by taking a zinc-cobalt bimetal-based zeolite imidazate metal organic framework material as a precursor, etching by using a tannic acid solution to obtain a macroporous structure; and after the niobium element is adsorbed, the porous carbon-coated cobalt elementary substance / niobium carbide heterojunction material can be prepared through high-temperature heat treatment. The material can be applied to a lithium-sulfur battery as a sulfur-based positive electrode carrier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy materials, and particularly to a porous carbon-coated cobalt metal / niobium carbide heterojunction material, a preparation method thereof, and an application thereof. Background Art

[0002] The rapid popularization of mobile electronic devices and new energy vehicles has led to an increasing social concern about energy storage technologies. As a relatively mature energy storage technology, rechargeable batteries have had multiple commercially successful systems in history, including nickel-metal hydride batteries, lead-acid batteries, and lithium-ion batteries. In particular, lithium-ion batteries have occupied a leading market position in the energy storage field in recent years. However, the actual energy density of current commercial lithium-ion batteries has approached the theoretical upper limit. To meet the demand for further improvement of the energy density of rechargeable batteries in the energy storage market, it is imperative to develop new rechargeable battery systems.

[0003] As a rechargeable battery system at the research forefront, lithium-sulfur batteries use sulfur and lithium as the electrochemically active materials of the positive and negative electrodes respectively, and have a theoretical energy density as high as 2600 Wh kg -1 . In addition, compared with the intercalation-type positive electrode of commercial lithium-ion batteries, the sulfur-based positive electrode raw materials of lithium-sulfur batteries are rich in sources and low in price, so they have significant cost advantages.

[0004] However, the current practical application of lithium-sulfur batteries is still restricted by a number of technical difficulties. On the positive electrode side, the poor electrical conductivity of the electrochemically active materials sulfur and lithium sulfide, the prominent electrode volume change during charge and discharge, the shuttle effect of the intermediate product long-chain polysulfide in the ether-based electrolyte, the sluggish kinetics in the solid-phase reaction stage, and many other factors have a negative impact on the performance of lithium-sulfur batteries. To overcome the above defects, developing a reasonable sulfur-based positive electrode carrier material is an effective way. Summary of the Invention

[0005] In order to overcome the defects existing in the above-mentioned prior art, the present invention provides a porous carbon-coated cobalt metal / niobium carbide heterojunction material, a preparation method thereof, and an application thereof, which are applied in the field of lithium-sulfur batteries, can effectively improve the electrochemical performance, have a simple synthesis process and are convenient for large-scale production.

[0006] That is, the present invention includes the following components.

[0007] (1) A porous carbon-coated cobalt metal / niobium carbide heterojunction material, characterized in that the material includes polyhedral hollow nitrogen-doped porous carbon, and cobalt metal / niobium carbide heterojunctions dispersed on the porous carbon.

[0008] (2) The porous carbon-coated cobalt metal / niobium carbide heterojunction material described in (1) is characterized in that, based on the total mass of the polyhedral hollow nitrogen-doped porous carbon, the content of cobalt element on the porous carbon is 2-30 wt.%, the content of niobium element is 2-30 wt.%, and the content of the cobalt metal / niobium carbide heterojunction is 1-60 wt.%.

[0009] (3) The porous carbon-coated cobalt metal / niobium carbide heterojunction material described in (1) is characterized in that, based on the total mass of the polyhedral hollow nitrogen-doped porous carbon, the ratio of cobalt element to niobium element, i.e., Co / Nb, is (1:0.5) to (1:3).

[0010] (4) The porous carbon-coated cobalt metal / niobium carbide heterojunction material described in (1) is characterized in that the specific surface area of the polyhedral hollow nitrogen-doped porous carbon is 300 m 2 g -1 or more, and the pore volume is 0.3 cm 3 g -1 or more.

[0011] (5) The preparation method of the porous carbon-coated cobalt metal / niobium carbide heterojunction material described in any one of (1)-(4) is characterized in that the preparation method comprises the following steps:

[0012] Using the zinc-cobalt bimetallic zeolitic imidazolate metal-organic framework material ZIF-ZnCo as a precursor, etching with tannic acid solution to obtain a pore structure, then adsorbing niobium element, and finally preparing the porous carbon-coated cobalt metal / niobium carbide heterojunction material by heat treatment.

[0013] (6) The preparation method of the porous carbon-coated cobalt metal / niobium carbide heterojunction material described in (5) is characterized in that the ZIF-ZnCo is synthesized by zinc acetate dihydrate, cobalt acetate tetrahydrate and 2-methylimidazole according to a molar ratio of (4.95-19.8):(0.55-2.2):(65-260), and the solvent dosage corresponding to every 9.9 mmol of zinc acetate dihydrate is 45-180 ml.

[0014] (7) The preparation method of the porous carbon-coated cobalt metal / niobium carbide heterojunction material described in (5) is characterized in that ZIF-ZnCo and tannic acid are dispersed in a solvent according to a mass ratio of (290-1160):(390-1560) for etching, the solvent dosage corresponding to every 580 mg of ZIF-ZnCo is 70-280 ml, and the etching time is 15-60 min.

[0015] (8)(5) The preparation method of the porous carbon-coated cobalt metal / niobium carbide heterojunction material is characterized in that niobium pentachloride and the etched ZIF-ZnCo are dispersed in a solvent according to a mass ratio of (20-80):(200-800) for niobium adsorption, wherein the solvent dosage corresponding to every 40 mg of niobium pentachloride is 45-180 ml, and the reaction is carried out at a temperature of 40-60 °C for 2-8 h.

[0016] (9)(5) The preparation method of the porous carbon-coated cobalt metal / niobium carbide heterojunction material is characterized in that in the heat treatment step, in an atmosphere of H2 / non-reactive gas, the temperature is raised to 830-1030 °C at a rate of 2-4 °C / min, held for 1.5-6 h, and after cooling, the porous carbon-coated cobalt metal / niobium carbide heterojunction material is obtained.

[0017] (10) A sulfur-based cathode, characterized in that it includes the porous carbon-coated cobalt metal / niobium carbide heterojunction material described in any one of (1)-(4) as the sulfur-based cathode carrier.

[0018] (11) A lithium-sulfur battery, characterized in that it includes the sulfur-based cathode described in (10).

[0019] (12) The application of the porous carbon-coated cobalt metal / niobium carbide heterojunction material described in any one of (1)-(4), characterized in that this material is used as the sulfur-based cathode carrier of a lithium-sulfur battery.

[0020] Effect of the invention

[0021] In the present invention, the porous carbon-coated cobalt metal / niobium carbide heterojunction material effectively utilizes the outstanding specific surface area and pore structure advantages of porous carbon, facilitating high-proportion sulfur loading. In addition, the construction of the cobalt metal / niobium carbide heterojunction enables the carrier material to have better performance in promoting the conversion kinetics of polysulfide lithium and inhibiting the shuttle effect compared to when loading a single type of adsorption-catalyst. Therefore, it can be suitably used as the sulfur-based cathode carrier of a lithium-sulfur battery.

[0022] The present invention also provides a preparation method of the porous carbon-coated cobalt metal / niobium carbide heterojunction material, which can prepare a metal metal / metal carbide heterojunction uniformly loaded on porous carbon, can construct new related heterojunction materials by adjusting the types of introduced metal elements, and has a simple synthesis process and is suitable for large-scale production. Brief description of the drawings

[0023] Figure 1 Transmission electron microscope (TEM) image and partial enlarged image of the porous carbon-coated cobalt metal / niobium carbide heterojunction material (Co / NbC@HNC) prepared in Example 1.

[0024] Figure 2Element distribution results of Co / NbC@HNC prepared in Example 1 observed by X-ray energy dispersive spectroscopy (EDS).

[0025] Figure 3 X-ray diffraction (XRD) patterns of Co / NbC@HNC prepared in Example 1 and the comparative materials.

[0026] Figure 4 Adsorption-desorption curves of Co / NbC@HNC prepared in Example 1 measured by nitrogen isothermal adsorption-desorption test.

[0027] Figure 5 Metal element content map of Co / NbC@HNC prepared in Example 1 tested by inductively coupled plasma spectroscopy (ICP-OES).

[0028] Figure 6 Projected density of states (PDOS) maps of Nb element in Co / NbC@HNC and the comparative material NbC@HNC prepared in Example 1 calculated according to density functional theory (DFT).

[0029] Figure 7 Rate performance curves of lithium-sulfur batteries prepared with Co / NbC@HNC and the comparative materials as sulfur-based cathode carriers in Example 1.

[0030] Figure 8 Cyclic capacity curves of lithium-sulfur batteries prepared with Co / NbC@HNC and the comparative materials as sulfur-based cathode carriers in Example 1.

[0031] Figure 9 Low-rate voltage-specific capacity curves of lithium-sulfur batteries prepared with Co / NbC@HNC prepared in Example 2 under high areal loading conditions.

[0032] Figure 10 Cyclic capacity curves of lithium-sulfur batteries prepared with Co / NbC@HNC prepared in Example 2 under high areal loading conditions. Detailed implementation manners

[0033] As a sulfur-based cathode carrier material, porous carbon has a high specific surface area and a rich pore structure, so it can provide sufficient sulfur-loading space. However, its disadvantage is that it cannot effectively adsorb and catalyze polysulfides. On the other hand, metallic elements or metal carbides are two common types of transition metal-based adsorption-catalysts in current research. However, when separately loaded on a porous carbon substrate, the promotion effect on the complex electrochemical reactions during the charge and discharge processes of lithium-sulfur batteries is often limited. Therefore, it is necessary to further optimize. In the present invention, by constructing a heterojunction of metallic elements / metal carbides, the interfacial charge is rearranged to enhance the activity of the adsorption-catalytic center, achieving a further breakthrough in electrochemical performance. Specifically, a reasonable heterojunction can cause the d-band center of a specific metal element to shift upward, thereby enhancing the bonding strength between the material and sulfur element, while weakening the S-S bond in LiPSs to enhance the chemisorption and significantly improve the surface catalytic effect, which can be determined according to the projected density of states (PDOS) results calculated by density functional theory (DFT).

[0034] Based on the above theoretical analysis, the present invention provides a porous carbon-coated cobalt / niobium carbide heterojunction material, which is used as the sulfur-based cathode carrier of a lithium-sulfur battery, effectively utilizing the sulfur storage advantage of porous carbon, and further achieving an effective improvement in electrochemical performance through the construction of a heterojunction adsorption-catalyst. The present invention will be described in detail below.

[0035] [Porous carbon-coated cobalt / niobium carbide heterojunction material]

[0036] The present invention is characterized in that it is a porous carbon-coated cobalt / niobium carbide heterojunction material, which includes polyhedral hollow nitrogen-doped porous carbon and cobalt / niobium carbide heterojunctions uniformly dispersed on the porous carbon.

[0037] In the present invention, the porous carbon used is polyhedral hollow nitrogen-doped porous carbon, which has a hollow structure and forms a cavity inside, thereby increasing the specific surface area of the material, providing more active sites for processes such as adsorption and catalysis. At the same time, the surface and interior contain rich pores, which contribute to the transport and diffusion of substances and improve the reaction performance of the material. The polyhedron includes octahedron, dodecahedron, octadecahedron, icosahedron, etc., which can be appropriately used within the range that does not damage the effect of the present invention. In the present invention, the dodecahedron is preferred.

[0038] The specific surface area of the polyhedral hollow nitrogen-doped porous carbon of the present invention is 100 m 2 g -1 or more, more preferably 200 m 2 g -1 or more, further preferably 300 m 2 g -1 or more. When it is lower than 100 m2 g -1 , which is easy to increase the polarization phenomenon of the electrochemical reaction. There is no special upper limit. In principle, the higher the better according to the specific preparation process; the pore volume is 0.1cm 3 g -1 Above, preferably 0.2 cm 3 g -1 More preferably 0.3 cm 3 g -1 Above, when below 0.1cm 3 g -1 , which can easily cause agglomeration of active materials. There is no particular upper limit. In principle, the higher the better, the better, depending on the specific preparation process. Although single-component porous carbon has a rich pore structure, due to the non-polar characteristics of pure carbon materials, the effect of inhibiting the shuttle effect is not obvious. Therefore, in the present invention, nitrogen is doped into the porous carbon to form a chemical bond with lithium polysulfide, thereby enhancing the anchoring effect on polysulfides. The doping amount of nitrogen element can be appropriately selected within the scope of the effect of the present invention, and is preferably 1wt.% to 30wt.% based on the total mass of the polyhedral hollow nitrogen-doped porous carbon.

[0039] In the present invention, by constructing a metal element / metal carbide heterojunction, the interfacial charge is rearranged to enhance the activity of the adsorption-catalytic center. To this end, cobalt element and niobium carbide are uniformly dispersed on porous carbon in the form of a heterojunction, wherein the heterojunction refers to a cobalt element with a particle size of nanometers and niobium carbide that is combined at the interface to form a structural composite material, and the cobalt element and niobium carbide are in a state of uniform mixing at a non-atomic scale. Since their respective chemical compositions and phase structures are still maintained, the activity of the adsorption-catalytic center can be enhanced through interfacial effects (such as electron transfer and stress regulation), thereby achieving the effect of improving the electrochemical performance of the present invention.

[0040] The porous carbon-coated cobalt element / niobium carbide heterojunction material of the present invention comprises nanoparticles formed by heterojunction of cobalt element and niobium carbide, wherein the particle size of the heterojunction nanoparticles is concentrated in 5 to 100 nm. The content of the cobalt element and the niobium carbide heterojunction formed on the polyhedral hollow nitrogen-doped porous carbon can be appropriately selected in consideration of the adsorption-catalytic effect and avoiding agglomeration. Generally speaking, it is preferably 1 to 60 wt.% based on the total mass of the polyhedral hollow nitrogen-doped porous carbon.

[0041] On the other hand, based on the total mass of the polyhedral hollow nitrogen-doped porous carbon, the content of cobalt on the porous carbon is preferably 2-30wt.%, and the content of niobium is preferably 2-30wt.%. Based on the viewpoint of balancing the probability of heterojunction formation and the uniformity of element distribution, the ratio of cobalt to niobium is preferably in the range of (1:0.5) to (1:3), and more preferably in the range of (1:1.2) to (1:3).

[0042] In the present invention, uniform dispersion refers to the fact that the heterojunction interface formed by cobalt element and niobium carbide is dispersed on the porous carbon substrate, which can be confirmed by observing the distribution of metal elements using EDS characterization technology.

[0043] Furthermore, the formation of the heterojunction between cobalt and niobium carbide can be determined by transmission electron microscopy and X-ray diffraction.

[0044] Specifically, when using a transmission electron microscope, the arrangement of metal atoms is directly observed through the high-resolution mode of the transmission electron microscope. If a heterogeneous interface is formed, lattice fringes with different interplanar spacings will be observed, that is, two different lattice structures will be seen in contact with each other at the interface, with obvious lattice mismatch and interface transition areas.

[0045] In the case of X-ray diffraction (XRD), since each crystal phase has its own specific diffraction peak, when two crystals form a heterogeneous interface, the characteristic peaks of the two phases will appear in the XRD spectrum, and the presence of the interface may cause changes in the position, intensity and width of the peaks. Therefore, if a heterostructure is formed, the XRD spectrum will show the diffraction peaks of cobalt and niobium carbide at the same time, and the peak shift caused by lattice distortion and other reasons can be observed.

[0046] [Preparation method of porous carbon-coated cobalt single substance / niobium carbide heterojunction material]

[0047] In order to achieve the effective formation of the heterojunction interface, the heat treatment parameters can be controlled to avoid the agglomeration of the transition metal-based materials and thus the interface contact probability of different phases being affected.

[0048] The present invention is preferably manufactured by the following method:

[0049] Zinc-cobalt bimetallic zeolite imidazolate metal-organic framework material (ZIF-ZnCo) was used as a precursor and etched with tannic acid solution to obtain a macroporous structure. After adsorbing niobium element, a porous carbon-coated cobalt element / niobium carbide heterojunction material was prepared by high-temperature heat treatment.

[0050] In the present invention, the large molecular weight anions of tannic acid can be adsorbed on the surface of ZIF-ZnCo, thereby maintaining the framework shape of the material. Through the etching effect of tannic acid, the wall thickness and pore size distribution of the hollow polyhedron can be regulated at the nanoscale to form a hierarchical porous structure, significantly increasing the specific surface area of the material. Further, the three-dimensional skeleton structure of the thus formed hollow polyhedron can buffer the volume change during charge and discharge processes and is applicable to energy storage systems with high-loading active substances.

[0051] Specifically, the specific steps for synthesizing ZIF-ZnCo are preferably as follows:

[0052] Zinc acetate dihydrate, cobalt acetate tetrahydrate, and 2-methylimidazole are dissolved in a solvent according to a molar ratio of (4.95 - 19.8):(0.55 - 2.2):(65 - 260), wherein the solvent dosage corresponding to every 9.9 mmol of zinc acetate dihydrate is 45 - 180 ml. After standing for 1 - 4 h, the precipitate is collected by centrifugation, washed, and dried. Among them, the solvent is preferably deionized water, and the particle size of the precursor material is adjusted by adjusting the solution concentration ratio.

[0053] Further, the specific steps for etching with the tannic acid solution are as follows:

[0054] ZIF-ZnCo and tannic acid are dispersed in a solvent according to a mass ratio of (290 - 1160):(390 - 1560) and thoroughly mixed, wherein the solvent dosage corresponding to every 580 mg of ZIF-ZnCo is 70 - 280 ml. After etching for 15 - 60 min, the precipitate is collected by centrifugation, washed, and dried. The solvent is preferably deionized water.

[0055] Further, the specific steps for adsorbing niobium element are as follows:

[0056] Niobium pentachloride and the etched ZIF-ZnCo are dispersed in a solvent according to a mass ratio of (20 - 80):(200 - 800) and thoroughly mixed, wherein the solvent dosage corresponding to every 40 mg of niobium pentachloride is 45 - 180 ml. After reacting at a temperature of 40 - 60 °C for 2 - 8 h, the precipitate is collected by centrifugation, washed, and dried. The solvent is preferably ethanol.

[0057] Further, the specific steps for high-temperature heat treatment are as follows:

[0058] The etched ZIF-ZnCo powder adsorbed with niobium element is fed into a heat treatment furnace with a H2 / inert gas atmosphere, heated to 830 - 1030 °C at a rate of 2 - 4 °C / min, held for 1.5 - 6 h, and then cooled to obtain a porous carbon-coated cobalt single crystal / niobium carbide heterojunction material. The inert gas atmosphere is preferably an Ar atmosphere.

[0059] Through the manufacturing method of the present invention, the metal single / metal carbide heterojunction is uniformly loaded on the porous carbon, enabling the rearrangement of interfacial charges to enhance the activity of the adsorption-catalysis center and improve the electrochemical performance. Further, new related heterojunction materials can be constructed by adjusting the types of introduced metal elements.

[0060] [Sulfur-based cathode carrier]

[0061] The porous carbon-coated cobalt single / niobium carbide heterojunction material of the present invention as described above can be applied to lithium-sulfur batteries as a sulfur-based cathode carrier.

[0062] The porous carbon-coated cobalt single / niobium carbide heterojunction material of the present invention can be made into a sulfur-based cathode carrier by conventional methods in the art, and further can be made into a battery by conventional methods. Specifically, it can be manufactured by the following method: After compounding the material with the electrochemically active substance sulfur by the melt diffusion method, conductive carbon and a binder are added, and then a sulfur-based cathode is prepared through processes such as stirring, homogenization, coating, and drying. A CR2032-type coin cell is assembled using a lithium metal sheet anode, a Celgard 2400 separator, and a DOL / DME electrolyte dissolved with 1M LiTFSI and 2 wt.% of LiNO3.

[0063] The above coin cell is placed on a battery testing system and charged and discharged at a set current rate (1C = 1675 mA g -1 ) within the working voltage range of 1.7V to 2.8V for electrochemical testing. The battery with the porous carbon-coated cobalt single / niobium carbide heterojunction material of the present invention can exhibit a specific capacity of 700 mAh g -1 during the 15th - 20th cycles at a 1C rate, and a specific capacity of 400 mAh g -1 or more during the 25th - 30th cycles at a 5C rate.

[0064] Further, the battery with the porous carbon-coated cobalt single / niobium carbide heterojunction material of the present invention can still have a capacity of up to 500 mAh g -1 or more after 600 cycles at a 1C current density, so it can be considered to have good cycle stability.

[0065] In addition, the battery with the porous carbon-coated cobalt single / niobium carbide heterojunction material of the present invention can also exhibit excellent electrochemical performance even under the condition of a high areal loading of more than 2 mg cm -2 .

[0066] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments. These embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation manners and specific operation processes are given. However, the protection scope of the present invention is not limited to the following embodiments.

[0067] Example 1

[0068] Preparation of Porous Carbon-Coated Cobalt Metal / Niobium Carbide Heterojunction Material

[0069] First, synthesize the ZIF-ZnCo precursor. Dissolve zinc acetate dihydrate, cobalt acetate tetrahydrate, and 2-methylimidazole in deionized water according to a molar ratio of 9.9:1.1:130. The amount of deionized water corresponding to every 9.9 mmol of zinc acetate dihydrate is 90 ml. After standing for 2 h, centrifuge to collect the precipitate, wash, and dry it.

[0070] Next, perform the etching operation with tannic acid solution. Disperse ZIF-ZnCo and tannic acid in deionized water according to a mass ratio of 580:780 and mix well. The amount of deionized water corresponding to every 580 mg of ZIF-ZnCo is 140 ml. After etching for 30 min, centrifuge to collect the precipitate, wash, and dry it.

[0071] Thereafter, perform the operation of adsorbing niobium element. Disperse niobium pentachloride and the etched ZIF-ZnCo in ethanol according to a mass ratio of 40:400 and mix well. The amount of ethanol corresponding to every 40 mg of niobium pentachloride is 90 ml. React at 50 °C for 4 h, then centrifuge to collect the precipitate, wash, and dry it.

[0072] Finally, perform the high-temperature heat treatment operation, that is, send the etched ZIF-ZnCo powder adsorbed with niobium element into a heat treatment furnace with a H2 / Ar atmosphere, heat it to 930 °C at a rate of 3 °C / min, hold for 3 h, and cool to obtain the porous carbon-coated cobalt metal / niobium carbide heterojunction material.

[0073] Material Characterization and Performance Testing

[0074] After the above material is compounded with the electrochemically active substance sulfur by the melt diffusion method, conductive carbon and binder are added, and a sulfur-based positive electrode is prepared through processes such as stirring, homogenizing, coating, and drying. The areal loading is fixed at about 1 mg cm -2 , using a lithium metal sheet negative electrode, a Celgard 2400 separator, and a DOL / DME electrolyte solution dissolved with 1 M LiTFSI and 2 wt.% LiNO3, assemble a CR2032 type coin cell. As shown in Figure 7 and Figure 8 The electrochemical tests show that the battery has good performance in specific capacity and cycling stability.

[0075] Figure 1 It can be observed that the morphology of Co / NbC@HNC is a polyhedron with a hollow structure, and transition metal-based nanoparticles are loaded on the carbon substrate. The lattice fringes with two different interplanar spacings shown in the enlarged view on the right confirm the existence of the cobalt / niobium carbide heterojunction.

[0076] Figure 2 The EDS elemental distribution results confirm that Co and Nb are uniformly dispersed and loaded on the nitrogen-doped porous carbon substrate.

[0077] Figure 3 The XRD pattern proves the existence of two phases, Co and NbC, in Co / NbC@HNC.

[0078] Figure 4 The curve in... shows that the specific surface area of Co / NbC@HNC is 372.3 m 2 g -1 , and the pore volume is 0.363 cm 3 g -1 .

[0079] Figure 5 It shows that the cobalt element content of Co / NbC@HNC is 11.09 wt.%, the niobium element content is 16.65 wt.%, and the ratio of the two is 1:1.5.

[0080] Figure 6 The theoretical calculation results confirm that the construction of a heterojunction by compounding Co on the basis of NbC can promote the upward shift of the d-band center of the Nb element, thereby enhancing the activity.

[0081] Comparative example

[0082] According to the same preparation method as in Example 1, the comparative materials Co@HNC and NbC@HNC were respectively fabricated. Among them, the difference between Co@HNC and Co / NbC@HNC is only that no Nb element was introduced during the synthesis process, and the difference between NbC@HNC and Co / NbC@HNC is only that no Co element was introduced during the synthesis process. The same battery as in Example 1 was fabricated using the above comparative materials and subjected to electrochemical tests.

[0083] As Figure 7 shown, compared with the sulfur-based cathode carrier loaded with a single type of transition metal-based adsorption-catalyst, Co / NbC@HNC has better performance in rate performance and can still provide a specific capacity of about 440 mAh g -1 at a high current density of 5C.

[0084] As Figure 8As shown, compared with the sulfur-based cathode carrier loaded with a single type of transition metal-based adsorption-catalyst, Co / NbC@HNC has better performance in cycling performance. At a current density of 1C, after 600 cycles, the average capacity decay rate is only 0.063%.

[0085] Example 2

[0086] The porous carbon-coated cobalt single substance / niobium carbide heterojunction material was fabricated according to the same preparation method as in Example 1, and the battery was fabricated according to the following method for electrochemical testing under high areal loading conditions.

[0087] After the above material was compounded with the electrochemically active substance sulfur by the melt diffusion method, conductive carbon and binder were added, and the sulfur-based cathode was prepared through processes such as stirring, homogenizing, coating, and drying. Areal loadings of 2.8 mg cm -2 and 3.4 mg cm -2 were used. A CR2032 coin cell was assembled using a lithium metal anode, a Celgard 2400 separator, and a DOL / DME electrolyte dissolved with 1M LiTFSI and 2 wt.% LiNO3.

[0088] As Figure 9 shown, even under high areal loading conditions, the sulfur-based cathode using Co / NbC@HNC can still provide a specific capacity of more than 1300 mAh g -1 at a current density of 0.1C.

[0089] As Figure 10 shown, under high areal loading conditions, the sulfur-based cathode using Co / NbC@HNC can still maintain a specific capacity of more than 800 mAh g -1 after 50 cycles at a current density of 0.2C.

[0090] In summary, the material prepared in the present invention effectively combines the advantages of porous carbon and cobalt single substance / niobium carbide heterojunction. The tannic acid-etched ZIF-ZnCo-derived porous carbon has a hollow structure, which is beneficial for storing active substances. At the same time, the cobalt single substance / niobium carbide heterojunction has better activity compared with a single type of adsorption-catalyst. Therefore, when this material is used as the sulfur-based cathode carrier of a lithium-sulfur battery, it shows good application potential.

[0091] The above are only the preferred embodiments of the present invention, and the present invention is not limited to other forms. Any person skilled in the art may use the disclosed technical content to make changes or modifications into equivalent embodiments with equivalent changes. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the technical solution content of the present invention still fall within the protection scope of the technical solution of the present invention.

Claims

1. A porous carbon-coated cobalt metal / niobium carbide heterojunction material, characterized in that, The material includes polyhedral hollow nitrogen-doped porous carbon and cobalt / niobium carbide heterojunctions dispersed in the porous carbon.

2. The porous carbon-coated cobalt metal / niobium carbide heterojunction material according to claim 1, characterized in that, Based on the total mass of the polyhedral hollow nitrogen-doped porous carbon, the content of cobalt element on the porous carbon is 2-30 wt.%, the content of niobium element is 2-30 wt.%, and the content of cobalt / niobium carbide heterojunctions is 1-60 wt.%.

3. The porous carbon-coated cobalt single substance / niobium carbide heterojunction material according to claim 1, wherein Based on the total mass of the polyhedral hollow nitrogen-doped porous carbon, the ratio of cobalt element to niobium element, i.e., Co / Nb, is (1:0.5)-(1:3).

4. The porous carbon-coated cobalt metal / niobium carbide heterojunction material according to claim 1, wherein The specific surface area of the polyhedral hollow nitrogen-doped porous carbon is 300 m 2 g -1 or more, and the pore volume is 0.3 cm 3 g -1 or more.

5. A method for preparing the porous carbon-coated cobalt metal / niobium carbide heterojunction material according to any one of claims 1-4, characterized in that, The preparation method includes the following steps: Using the zinc-cobalt bimetallic zeolitic imidazolate metal-organic framework material ZIF-ZnCo as a precursor, etching with tannic acid solution to obtain a pore structure, then adsorbing niobium element, and finally preparing a porous carbon-coated cobalt / niobium carbide heterojunction material through heat treatment.

6. The preparation method of the porous carbon-coated cobalt single substance / niobium carbide heterojunction material according to claim 5, characterized in that, The ZIF-ZnCo is synthesized by zinc acetate dihydrate, cobalt acetate tetrahydrate, and 2-methylimidazole according to a molar ratio of (4.95-19.8):(0.55-2.2):(65-260), and the solvent dosage corresponding to every 9.9 mmol of zinc acetate dihydrate is 45-180 ml.

7. The preparation method of the porous carbon-coated cobalt single substance / niobium carbide heterojunction material according to claim 5, wherein, ZIF-ZnCo and tannic acid are dispersed in a solvent according to a mass ratio of (290-1160):(390-1560) for etching, the solvent dosage corresponding to every 580 mg of ZIF-ZnCo is 70-280 ml, and the etching time is 15-60 min.

8. The method for preparing the porous carbon-coated cobalt element / niobium carbide heterojunction material according to claim 5, characterized in that: Niobium pentachloride and the etched ZIF-ZnCo are dispersed in a solvent according to a mass ratio of (20-80):(200-800) for niobium adsorption, the solvent dosage corresponding to every 40 mg of niobium pentachloride is 45-180 ml, and the reaction is carried out at 40-60 °C for 2-8 h.

9. The preparation method of the porous carbon-coated cobalt single substance / niobium carbide heterojunction material according to claim 5, wherein In the heat treatment step, in an H2 / inert gas atmosphere, the temperature is raised to 830-1030 °C at a rate of 2-4 °C / min, held for 1.5-6 h, and after cooling, a porous carbon-coated cobalt / niobium carbide heterojunction material is obtained.

10. A sulfur-based positive electrode, characterized in that, Including the porous carbon-coated cobalt / niobium carbide heterojunction material described in any one of claims 1-4 as a sulfur-based cathode carrier.

11. A lithium-sulfur battery, characterized in that, Including the sulfur-based cathode described in claim 10.

12. Use of the porous carbon-coated cobalt single substance / niobium carbide heterojunction material according to any one of claims 1-4, characterized in that, The material is used as a sulfur-based cathode carrier for lithium-sulfur batteries.